2014
DOI: 10.1021/jp410565e
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous RVO4 Photocatalyst Systems (R = Y, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu)

Abstract: By resorting on first-principles dynamical simulations and supporting experiments, we present a systematic and detailed inspection of a new series of inhomogeneous photocatalytic RVO4 systems (R = Y, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu), where YVO4 is the most representative member. We evidenced a carrier separation, promoted by Pt acting as a cocatalyst, which allows for a clear understanding of the electronic properties of these inhomogeneous systems. These, in turn, are shown to be of crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Interestingly, we found that after releasing pressure, our samples remain in the HP phase. This allows us to determine the band gap of the metastable monazite-type polymorph at ambient pressure, with E gap = 3.26 (2) eV. This value is probably more suitable for many photocatalytic applications than that of zircon-type NdVO 4 .…”
Section: High-pressure Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, we found that after releasing pressure, our samples remain in the HP phase. This allows us to determine the band gap of the metastable monazite-type polymorph at ambient pressure, with E gap = 3.26 (2) eV. This value is probably more suitable for many photocatalytic applications than that of zircon-type NdVO 4 .…”
Section: High-pressure Studiesmentioning
confidence: 99%
“…Trivalent metal orthovanadates have been constantly studied during the last decade because of their optical properties, which makes them appropriate for many different technological applications. Such applications go from photocatalytic water purification and hydrogen production to scintillators, phosphors, solid-state lasers, magnetoelectric, and medical applications [1][2][3][4][5][6]. Neodymium vanadate (NdVO 4 ) is one of the most promising orthovanadates for the development of technological applications [1][2][3][4][5][6], for which an accurate knowledge of NdVO 4 optical properties is a fundamental requisite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the EPR g-factors, g // = 3.544, g \ = 7.085 for the Er 3+ in the YVO 4 crystal, and the g // =6.35, g \ = 4.53 for the Er 3+ in ScVO 4 crystal, indicate the opposite anisotropy of the g-factors [22,23]. (2) As to the two systems, the lowest states have been attributed to the Kramers doublet 2 C 6 from the EPR parameters, which imply the rule that the average g-tensor g av (= |g // |/3 + 2|g \ |/3) of the tetragonal Er 3+ centres in the YVO 4 and ScVO 4 will be close to the theoretical value g av (g av % 5.976)…”
mentioning
confidence: 98%
“…Introduction Trivalent rare-earth (RE) ions doped in vanadates have received considerable attention because of the wide applications such as in phosphors, display monitors, X-ray imaging, lasers, and amplifiers for fiber-optic communication [1][2][3][4][5][6][7][8][9][10][11]. For instance, Eu 3+ -ion activated YVO 4 can be utilized as a red phosphor in a cathode ray tube (CRT), and as a scintillator in medical image detector [3][4][5][6][7][8].…”
mentioning
confidence: 99%